Developing Kampoeng Kepiting Ecotourism Tuban using 4A Components - I Wayan Eka Adnyana; I Ketut Budarma; Ni Gst Nym Suci Murni (Catuspata Press, 2022)
Purpose: The purpose of this research is to examine the position of Kampoeng Kepiting Ecotourism Tuban, Bali, Indonesia, through analysis of tourism area life cycle and to design a model for development and innovation of Kampoeng Kepiting Tuban Bali based on the study of attractions, amenities, accessibility, and ancillary component (4As). Research methods: The primary data of this study are collected through involved observation and interviews. The secondary data for this study are from literature study and documentation. Findings: Kampoeng Kepiting Ecotourism Tuban Bali was in stagnation phase. Efforts of development are needed so that the destination does not reach the decline phase. Development model consists of main elements, concentration elements and supporting elements. Implications: The three elements are combined and form a development model of Kampoeng Kepiting Ecotourism Tuban Bali to overcome the stagnation phase so as not to reach the decline phase.